How do you dance? - Heder, Thyra (Abrams Books for Young Readers, 2019)
There are so many ways to dance! You can jiggle or wiggle or stomp. You can bop or bounce or go completely nuts. You can dance at the market or the bus stop, with your fingers or your face. You can dance because you're happy or even because you're sad. But what's the best way to dance? Exactly how you want to!"--